An analytical approach for the sizing and siting of battery-sourced inverters in distribution networks - Jamali, A.A. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents an analytical approach to find the optimum sizes and locations of battery-sourced inverters (BSI) in electrical distribution networks. To find optimum sizes and locations of BSI units, two indices, namely, minimum power injection (MPI), and minimum active power loss index (MAPLI) are used. BSI units can supply active and reactive power, are used to improve system voltage profile and reduce system losses. To investigate the dynamic effects, instead of conventionally used fixed peak load, a 24-hour time varying load model is used. To supply active and reactive power, BSI units are attached to all buses, but at one bus each time, with sizes starting from 0 and are further increased with a rate of 0.5 KVA, meanwhile the two indices are calculated for every bus for each hour. Method is tested on IEEE-33 bus test distribution network and results are presented. The results show that utilization of BSI can improve the voltage profile and can reduce the system losses up to 78 in distribution networks. The study also suggests that best time for utilizing of stored energy is during the peak load hours. © 2016 IEEE.